2012
DOI: 10.3346/jkms.2012.27.9.1091
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Distribution of Human Papillomavirus Infection in Korean Women as Determined by Restriction Fragment Mass Polymorphism Assay

Abstract: The development of a prophylactic vaccine that targets human papillomaviruses (HPV) 6, 11, 16, and 18 to prevent cervical cancer has increased interest in the ethnic and geographical distributions of HPV genotypes. We investigated HPV prevalence and type distribution by restriction fragment mass polymorphism (RFMP) testing a total of 60,775 specimens (aged 18-79 yr, median 44) taken from liquid-based cytology. Overall HPV positive rate of total patients was 34.2%. Among the positive patients, 87.7% was single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
40
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 31 publications
7
40
2
Order By: Relevance
“…As expected, we found that the most common genotypes HPV16 and HPV18 dominated among the 38 HPV-positive women in Da Nang, a finding that is similar to previous results reported from other places in Vietnam (10) and in other countries (4,13,14). About half of the 38 HPVpositive women in Da Nang were infected with only HPV 16 or 18, or both, and the rest with other risk types of HPV.…”
Section: Discussionsupporting
confidence: 80%
“…As expected, we found that the most common genotypes HPV16 and HPV18 dominated among the 38 HPV-positive women in Da Nang, a finding that is similar to previous results reported from other places in Vietnam (10) and in other countries (4,13,14). About half of the 38 HPVpositive women in Da Nang were infected with only HPV 16 or 18, or both, and the rest with other risk types of HPV.…”
Section: Discussionsupporting
confidence: 80%
“…As mentioned previously, the present study found that HPV infection rate showed an approximate U-shaped curve in terms of age: the infection rate of women younger than 25 years was significantly higher than in other age groups (c 2 = 22.747, P = 0.000 < 0.05) and the infection rate in women older than 55 years also showed an increase. These results are similar to the outcomes of Yip et al (2010) and Lee et al (2012). As a means of analyzing the reasons for these outcomes, it may be that young women have a more active sex life; HPV infection is closely related to sexual activities.…”
Section: Discussionsupporting
confidence: 72%
“…In our study population the overall prevalence of infections with any HPV type (39.6%) and prevalence of HR-HPV (29%) were higher in comparison with other studies (Masia et al, 2009;Lee et al, 2012). The six most prevalent HR-HPV types were HPV-16, 31, 51, 18, 52 and 58 in descending orders.…”
Section: Discussioncontrasting
confidence: 59%
“…Then we noted a gradual decrease in incidence of HPV infection up to the age of 45 years. This pattern is observed in the most studies all over the world, although second peaks are sometimes observed in older women (Munoz et al, 2004;Franceschi et al, 2006;Trottier and Franco, 2006;Lee et al, 2012). This decrease in HPV infection prevalence with age may be explained by the fact in most cases HPV infection is self-limited and the virus is cleared by the host innate immune response (Ho et al, 1998;Stanley, 2006;Datta et al, 2012).…”
Section: Discussionmentioning
confidence: 76%